Focal Epithelial Hyperplasia. A Case Report - Rafael Pila Pérez; Margarita Pila Peláez; Rafael Pila Peláez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Focal epithelial hyperplasia, also known as Heck's disease, is relatively rare, occurring mostly in children and adolescents. A case of a 20 year-old female patient treated at the Manuel Ascunce Domenech University Hospital in Camagüey due to papular lesions, which had evolved for ten months, is presented. Other viral diseases were ruled out; however based on histological studies, it was concluded that she suffered from Heck disease, which is frequently treated by dentists, but little known among pediatricians, internists and dermatologists. Because of its etiology, many cases are related to human papilloma virus infection. When the disease evolves, treatment can involve excision, laser surgery or cryotherapy. The latter method was used in this patient with satisfactory results, as she is completely asymptomatic.